Geochemical Assessment of Soils around Metal Recycling Industrial Areas in Ikorodu, Southwestern Nigeria (Global Journal of Science Frontier Research, 2017)
Baseline geochemical assessment of an area within latitude 006 o 43 1 N and 003 o 44 1 N and longitude 003 o 31 1 E and 003 o 37 1 E was carried out in other to provide information on the rate of contamination/ pollution caused to the soils by the iron and steel industries` activities around Ikorodu area. 11 soil samples were collected, prepared and analysed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Interpretation of the analysis results was carried out for their metal contents. Lead has the highest concentrations in soils (9945ppm) while Manganese was the most widely distributed metal in the area of study with a mean concentration value of 8414ppm. Further geochemical evaluation of the soils using Geo-accumulation Index, Enrichment Factor, Contamination Factor, and Pollution Load Index, revealed significant concentration of lead and zinc in the environmental media from within the study area while the other elements have minimal concentration in the environmental media studied.
Keywords: ikorodu area; geochemical; geo-accumulation; contamination; enrichment; pollution